Effect of Fragility on Growth and Poverty in Nigeria: A Disaggregate State-Level Analysis (2023)
Why some nations are wealthier than others are one of the most contentious and enigmatic questions in international development economics. This has necessitated plausible explanations for the reasons behind Africa's poor development record over the past 50 years. Among other factors, fragility arising from different conflicts in African countries has been ranked as a key factor that undermines the development of the continent. Nigeria found itself in this set due to growing conflicts in different parts of the country. Consequently, fragility worsened the country's development due to the huge associated economic and social costs. More so, conflict-affected countries are characterized by the worst socio-economic outcomes. Hence, existing studies have been preoccupied with the understanding of the relationship between fragility and economic growth as well as fragility and poverty. To provide evidence in the context of Nigeria, this paper, therefore, empirically investigated the fragility-growth nexus, as well as the fragility-poverty nexus, in a sample of 36 states and the Federal Capital Territory (FCT) in Nigeria. We further considered the macroeconomic and socio- political relationships in fragile and non-fragile states of Nigeria. Using data covering the period between 2011 and 2015, both the static approach (Ordinary Least Squares, Fixed Effect, and Random Effect) and the dynamic approach (Difference and System Generalized Method of Moments) were explored to provide answers to some key questions in the study. The results showed that the neoclassical and socio-political approaches complement each other. Specifically, fragility significantly weakened economic growth and further worsened poverty levels among the states. This suggests that conflict-related fragility creates an unstable environment that discourages economic activities and aggravates hunger among the population. More so, the results indicated that only debt enhances economic growth while income reduces poverty in both fragile and non-fragile states. Hence, conflict resolution is crucial to addressing conflicts in different parts of the country. Also, the country needs to explore various strategies (security infrastructure, and human capital) to overcome fragility, enhance economic growth, and combat poverty.